Identification of Freshwater Mollusk in the Fisheries and Marine Science Faculty’s Dam, Riau University, Pekanbaru - Christina Panggabean; Efawani '; Eddiwan ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2017)
Dam in the Fisheries and Marine Science Faculty Riau University is inhabited by many types of aquatic organism, included mollusk. To understand the types of freshwater mollusk present in the dam, a study was conducted in May to June 2016. Samplings were done for three days. There were two sampling stations namely Station 1 (in the dam) and Station 2 (in the dam’s outlet). Mollusks were captured directly by hand or they were picked up from sediment sampled using shovel. The mollusks were then photographed and identified Results shown that there were2 classes, 3 ordos, 6 families, 6 genus, and 7 species. They were Lymnaea persica, Gyraulus sp, Bellamyasp, Pilaglobosa, Thiara (Sernjyla) riqueti, Melanoides prashadi, and Elliptio producta. The value of water qualityparameters measured were temperature 28 oC, transperancy 42.5 cm, depth 20-150 cm, pH 5, dissolved oxygen 3.27-8.26 mg/L and free carbondioxide 7.1-11.9 mg/L.Keywords : Freshwater Mollusk, Dam, Pila sp, Bellamnya sp, Gyraulus sp